Exploring the causal relationship between inflammatory cytokines and intrahepatic cholangiocarcinoma: a Mendelian randomization study - Yue Tang; Jialu Chen; Delong Qin; Zonglong Li; Xinjian Xu; Zhaohui Tang (Holistic Integrative Oncology)
Abstract Background Intrahepatic cholangiocarcinoma (ICC) is a malignant tumor that begins in the bile duct epithelium and is associated with chronic inflammation. Research on the connections between ICC and various inflammatory markers, as well as their mechanisms, is limited. Although some associations have been identified, establishing a direct causal relationship between specific inflammatory factors and ICC risk has proven challenging. This study aims to use Mendelian randomization analysis to explore these causal relationships, offering insights into the biological mechanisms at play and potential therapeutic targets. Methods The study used Mendelian two-sample randomization, drawing on inflammatory cytokine data from a genome-wide association study (GWAS) involving 8,293 healthy participants and cases of ICC. The primary method for exploring the causal relationship between exposure and outcome was inverse-variance weighting. To enhance the robustness of the findings, multiple sensitivity analyses were conducted. Results The study suggests a possible causal link between Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand (TRAIL) and ICC. Inverse variance weighting analysis revealed that higher levels of TRAIL are associated with a reduced risk of ICC (OR: 0.65, 95% CI: 0.47-0.89, p < 0.01). This relationship held true across various sensitivity analyses, reinforcing the hypothesis that TRAIL may play a role in ICC development. In addition, the study identified associations between ICC and other inflammatory markers, including GRO-α, IL-9, MCP-3, M-CSF, and EOTAXIN. Conclusions This study found that higher levels of TRAIL are associated with a reduced risk of ICC, while the occurrence of ICC might cause significant abnormalities in GRO-α, EOTAXIN, and IL-9 levels. Inflammatory factors could serve as potential markers or predictors for ICC. However, these findings need to be validated through further large-scale, multicenter studies, and a deeper understanding of how inflammatory factors specifically influence ICC is required.